Activities Online and Compulsive Internet Use in Primary School-Aged Children: Whether and How it Has Changed during the COVID-19 Pandemic? - Jusienė, Roma; Breidokienė, Rima; Laurinaitytė, Ilona; Pakalniškienė, Vilmantė (Information & Media, 2022)
There has been a growing concern among researchers about the use of various information technologies with screens and the Internet by children and adolescents over the past decade. Researchers are concerned that such type of activities can have negative consequences for mental health. Recent studies reveal that Internet use and screen time increased due to the quarantine restrictions, lockdowns and therefore distance education during the COVID-19 pandemic. This study aims: 1) based on parental reports, to find out the changes in screen time, the online activities and the compulsive Internet use (CIU) of 10-11 years old children during the quarantine due to the COVID-19 pandemic; 2) to determine the links between children’s CIU and the screen time, online activities, children’s gender and their parents’ education. The results of this study showed that screen time was longer and children’s CIU scores were significantly higher in Spring 2020 if to compare to Autumn 2019. Boys were reported to have higher CIU scores than girls. Children’s CIU was significantly predicted by overall screen time and online activities for entertainment, especially when during quarantine.